Water Scarcity as a Non-traditional Threat to Security in the Middle East. (June 2017) - El-Sayed, Mustapha Kamel; Mansour, Rasha Soheil
The article aims to explore the securitisation of water in the Nile basin. As in the wider Middle East, the securitisation of water occurred in the context of larger political grievances, inherited from colonial times. The trigger in all cases has been water scarcity. The securitising actors in all cases were decision-makers; in the case of the Tigris–Euphrates basin, NGOs and human rights activists have also emerged as securitising actors. The target audiences in all cases included the national public and international public opinion, as well as decision-makers in donor countries, especially in the case of the Tigris–Euphrates and Nile basins. Several securitisation mechanisms have been used simultaneously in all cases; in the case of the West Bank Aquifer, for example, resource capture (structural securitisation) went hand in hand with joint water management committees (institutional securitisation). In all cases, language played a crucial role in the securitisation of water resources, especially in the cases of Egypt and Israel, where the symbolic value of water and land are closely tied with religious traditions inherited from ancient times.